Self‐transducible LRS‐UNE‐L peptide enhances muscle regeneration. Issue 2 (17th February 2022) - Baek, Mi‐Ock; Cho, Hye‐Jeong; Min, Do Sik; Choi, Cheol Soo; Yoon, Mee‐Sup
Abstract: Background: Muscle regeneration includes proliferation and differentiation of muscle satellite cells, which involves the mammalian target of rapamycin (mTOR). We identified the C‐terminal unique attached sequence motif (UNE) domain of leucyl‐tRNA synthetase (LRS‐UNE‐L) as an mTORC1 (mTOR complex1)‐activating domain that acts through Vps34 and phospholipase D1 (PLD1) when introduced in the form of a muscle‐enhancing peptide. Methods: In vitro Vps34 lipid kinase assay, phosphatidylinositol 3‐phosphate (PI(3)P) measurement, in vivo PLD1 assay, and western blot assay were performed in HEK293 cells to test the effect of the LRS‐UNE‐L on the Vps34‐PLD1‐mTOR pathway. Adeno‐associated virus (AAV)‐LRS‐UNE‐L was transduced in C2C12 cells in vitro, in BaCl2 ‐injured tibialis anterior (TA) muscles, and in 18‐month‐old TA muscles to analyse its effect on myogenesis, muscle regeneration, and aged muscle, respectively. The muscle‐specific cell‐permeable peptide M12 was fused with LRS‐UNE‐L and tested for cell integration in C2C12 and HEK293 cells using FACS analysis and immunocytochemistry. Finally, M12‐LRS‐UNE‐L was introduced into BaCl2 ‐injured TA muscles of 15‐week‐old Pld1 +/+ or Pld1 −/− mice, and its effect was analysed by measurement of cross‐sectional area of regenerating muscle fibres. Results: The LRS‐UNE‐L expression restored amino acid‐induced S6K1 phosphorylation in LRS knockdown cells in a RagD GTPases‐independent manner (421%, P = 0.007 vs. LRS knockdown control cells). The LRS‐UNE‐L domain was directly bound to Vps34; this interaction was accompanied by increases in Vps34 activity (166%, P = 0.0352), PI(3)P levels (146%, P = 0.0039), and PLD1 activity (228%, P = 0.0294) compared with amino acid‐treated control cells, but it did not affect autophagic flux. AAV‐delivered LRS‐UNE‐L domain augmented S6K1 phosphorylation (174%, P = 0.0013), mRNA levels of myosin heavy chain (MHC) (122%, P = 0.0282) and insulin‐like growth factor 2 (IGF2) (146%, P = 0.008), and myogenic fusion (133%, P = 0.0479) in C2C12 myotubes. AAV‐LRS‐UNE‐L increased the size of regenerating muscle fibres in BaCl2 ‐injured TA muscles (124%, P = 0.0279) ( n = 9–10), but it did not change the muscle fibre size of TA muscles in old mice. M12‐LRS‐UNE‐L was preferentially delivered into C2C12 cells compared with HEK293 cells and augmented regeneration of BaCl2 ‐injured TA muscles in a PLD1‐dependent manner (116%, P = 0.0022) ( n = 6). Conclusions: Our results provide compelling evidence that M12‐LRS‐UNE‐L could be a muscle‐enhancing protein targeting mTOR.